2022
DOI: 10.1049/ntw2.12033
|View full text |Cite
|
Sign up to set email alerts
|

MOTS‐ACO: An improved ant colony optimiser for multi‐objective task scheduling optimisation problem in cloud data centres

Abstract: Task scheduling in cloud data centres is an optimisation problem that aims to minimise power consumption and task makespan as well as ensures the quality of service delivered to cloud consumers. Although there are several existing task scheduling approaches, these methods mainly focus on optimising makespans of tasks while ignoring critical issues. This paper presents a comprehensive multi-objective task scheduling model based on an improved Ant Colony Optimisation (ACO) algorithm, referred to as MOTS-ACO. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Objectives of resource scheduling algorithms modeled by diferent nature-inspired algorithms [7] Adaptive PSO Makespan, throughput, resource utilization [9] MCFCM-PSO Load balancing, makespan [10] PSO-RDAL Makespan, response time, penalty cost, total execution cost [11] CR-PSO Makespan, execution time, execution cost, energy consumption [5] GA-ACO Response time, task completion time, throughput [12] PSO-ACO Makespan, resource utilization, total computation cost [13] CCSA Makespan, overall cost [14] MOTS-ACO Makespan, turnaround time, power consumption [15] EDA-GA Task completion time, load balance of tasks [16] EPETS Energy consumption [17] MVO-GA Task transfer time [18] GACCRATS Makespan, customer satisfaction [19] MGGS Makespan, response time, QoS [20] OCSA Makespan, cost [24] CGA Task completion time, total execution cost [25] IWC Task scheduling time, scheduling cost [26] SLNO Energy, power consumption, resource utilization [27] GCWOAS2 Task completion time, load balance of virtual resources [28] GAGELS Makespan, resource utilization [29] DILS Makespan, learning rate…”
Section: References Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Objectives of resource scheduling algorithms modeled by diferent nature-inspired algorithms [7] Adaptive PSO Makespan, throughput, resource utilization [9] MCFCM-PSO Load balancing, makespan [10] PSO-RDAL Makespan, response time, penalty cost, total execution cost [11] CR-PSO Makespan, execution time, execution cost, energy consumption [5] GA-ACO Response time, task completion time, throughput [12] PSO-ACO Makespan, resource utilization, total computation cost [13] CCSA Makespan, overall cost [14] MOTS-ACO Makespan, turnaround time, power consumption [15] EDA-GA Task completion time, load balance of tasks [16] EPETS Energy consumption [17] MVO-GA Task transfer time [18] GACCRATS Makespan, customer satisfaction [19] MGGS Makespan, response time, QoS [20] OCSA Makespan, cost [24] CGA Task completion time, total execution cost [25] IWC Task scheduling time, scheduling cost [26] SLNO Energy, power consumption, resource utilization [27] GCWOAS2 Task completion time, load balance of virtual resources [28] GAGELS Makespan, resource utilization [29] DILS Makespan, learning rate…”
Section: References Methodologymentioning
confidence: 99%
“…It was compared over MO-ACO, Min-Min, and ACO algorithms, and the results showed that CCSA outperforms existing algorithms. In [14], scheduling approach designed by updating pheromone leads to increase in acceleration of ant exploration in solution space. MOTS-ACO was used as methodology for designing scheduling problem.…”
Section: Related Workmentioning
confidence: 99%
“…It specifies that 2 instances of type1 virtual machine can be executed, but if it supposes there are continuous type 1 request, then the type 1 and type 2 instances will be pushed to a starvation state. This is the problem considered and solved [20][21][22][23][24][25].…”
Section: Literature Surveymentioning
confidence: 99%
“…The results revealed that FPSO-GA had a fuzzy nature, which proved that it outperforms the existing approaches by efficiently balancing the load among VMs. In [ 22 ], the authors formulated an efficient power-aware task scheduling algorithm developed using a modified ACO approach. This algorithm was modeled based on updating pareto by accelerating the convergence using adaptive probability distribution.…”
Section: Related Workmentioning
confidence: 99%